Acoustic Observation of Zooplankton Using High Frequency Sonar (Observasi Akustik Zooplankton Menggunakan Sonar Frekuensi Tinggi) - Henry M Manik (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2015)
Underwater acoustic sampling techniques provide an advantage over traditional net-sampling for zooplankton research. The research presents a methodology for extracting both biological and physical information from high frequency sonar. These methods can easily provide the information that will improve our understanding of the spatial and temporal distribution of zooplankton. Measured acoustic data converted into biological organisms and numerical physics-based scattering models were used in this research. The numerical backscattering process was modeled using the Distorted-Wave Born Approximation (DWBA) to predict the amount of sound scattered by a weakly scattering animal. Both acoustic measurement and DWBA modeled scattering patterns showed that acoustic scattering levels are highly dependent on zooplankton orientation. The acoustic backscattering from zooplankton depends on the material properties (i.e. the sound speed and density of the zooplankton), the shape and size, and the orientation relative to the incident acoustic wave. DWBA model significantly improve the accuracy and precision of zooplankton acoustic surveys. Zooplankton data measurement and DWBA model analysis provide a basis for future acoustical studies.